2016
DOI: 10.1007/s13197-016-2266-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of popping and fermentation on proximate composition, minerals and absorption inhibitors, and mineral bioavailability of Amaranthus caudatus grain cultivated in Ethiopia

Abstract: This study evaluated the effect of popping and fermentation on the chemical composition of three types of grains cultivated in Ethiopia. Proximate composition, minerals and mineral absorption inhibitors were analyzed. Popping caused a decrease in protein content by 4 % and an increase in fat, ash, acid detergent fiber (ADF) and neutral detergent fiber (NDF) contents by 12, 10, 15 and 67 %, respectively. While fermentation increased protein, fat and ash content by 3, 22 and 14 %, respectively but did not signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…This higher phytate degradation in the late phase of spontaneously fermented amaranth flour may be explained by the fact that microorganisms naturally present in the flour may have had further phytase activity at a lower pH. Amare et al . reported a 77% reduction in phytate after spontaneous fermentation of amaranth flour for 48 h at 22 °C; this reduction may be due to the activation of endogenous phytase or the action of exogenous phytase released by microorganisms naturally present in flours when a favorable pH was reached.…”
Section: Discussionmentioning
confidence: 99%
“…This higher phytate degradation in the late phase of spontaneously fermented amaranth flour may be explained by the fact that microorganisms naturally present in the flour may have had further phytase activity at a lower pH. Amare et al . reported a 77% reduction in phytate after spontaneous fermentation of amaranth flour for 48 h at 22 °C; this reduction may be due to the activation of endogenous phytase or the action of exogenous phytase released by microorganisms naturally present in flours when a favorable pH was reached.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that phytate can impede the absorption of iron and other micro-and macro-nutrients from the gut. This problem can be resolved, however, by applying homemade processing, such as soaking, germinating, and fermenting [8,9]. Therefore, we believe that the result obtained in this study was related with homemade processing applied to amaranth grain that decreased the phytate level and enhanced the absorption of iron and other micro-and macro-nutrients.…”
Section: Plos Onementioning
confidence: 72%
“…Research on the nutritional value of amaranth and methods to decrease phytate level has been performed [8,9]. However, few investigations exist focusing on the effect of processed amaranth in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a successful popping of feedstuff to happen, a temperature between 160–193 °C is recommended, thereafter it is then cooled down gradually using mechanical cooling, as done in roasting. Several authors reported that popping reduces anti-nutritional factors, such as phytic acids in amaranth grains but results in a decrease in protein content which might be because some amino acids are very sensitive to heat [ 76 , 77 , 78 ]. However, the decrease in phytic acid content during the popping method results in more bioavailability of protein and minerals, and an increased level of carbohydrates [ 78 , 79 ].…”
Section: Processing Methods Used To Reduce Anti-nutritional Factormentioning
confidence: 99%